Biotechnology, patents and human rights in Europe : innovations concerning the human body - Żakowska-Henzler, Helena; Zemła-Pacud, Żaneta; Zimny, Tomasz (Edward Elgar Publishing, 2023)
"This innovative book explores the complex interplay between intellectual property for biotechnological innovations and human rights. Examining the clash between the drive to incentivise innovations that can fulfil human needs and the desire to grant global access to healthcare technologies, it presents thoughtful solutions to the challenges of protecting the human rights of all parties impacted by biotechnological patents and other relevant IP rights. After laying out the essential biotechnological innovations of the last 40 years, the authors conduct an in-depth analysis of European exclusive rights relating to biotechnology and healthcare, with particular attention to five key European jurisdictions - France, Germany, Italy, Poland and the UK. Delving into complex legal and ethical disputes over the rights to privacy, integrity, autonomy, health and science, the book argues for a more balanced patent system, protecting both human rights and intellectual property. This book will be a thought-provoking read for legal scholars, practitioners and policy-makers in the fields of biotechnology, pharmaceutical law, human rights law and intellectual property law. With its in-depth discussion of cutting-edge advances in biotechnology and the laws related to it, it will also prove enlightening for scholars and students interested in engaging with the field for the first time"--